Marine pharmacology in 2018: Marine compounds with antibacterial, antidiabetic, antifungal, anti-inflammatory, antiprotozoal, antituberculosis and antiviral activities; affecting the immune and nervous systems, and other miscellaneous mechanisms of action. (September 2022) - Mayer, Alejandro M.S.; Pierce, Marsha L.; Howe, Katelyn; Rodríguez, Abimael D.; Taglialatela-Scafati, Orazio; Nakamura, Fumiaki; Fusetani, Nobuhiro
Abstract: The 2018 marine pharmacology literature review represents a continuation of the previous 11 reviews of a series initiated in 1998. Preclinical marine pharmacology research during 2018 was performed by investigators in 44 countries and contributed novel pharmacology for 195 marine compounds. The peer-reviewed marine natural products pharmacology literature reported antibacterial, antifungal, antiprotozoal, antituberculosis, and antiviral activities for 53 compounds, 73 compounds which presented antidiabetic and anti-inflammatory activities as well as affecting the immune and nervous system, while in contrast 69 compounds were reported to show miscellaneous mechanisms of action which may contribute upon further investigation to several pharmacological classes. Thus, in 2018, the preclinical marine natural product pharmacology pipeline continued to report novel pharmacology as well as new lead compounds for the clinical marine pharmaceutical pipeline, which currently contributes to therapeutic strategies for several disease categories.